2020
DOI: 10.1175/jas-d-20-0131.1
|View full text |Cite
|
Sign up to set email alerts
|

Smoke with Induced Rotation and Lofting (SWIRL) in the Stratosphere

Abstract: The Australian bushfires of 2019/20 produced an unusually large number of pyrocumulonimbus (pyroCb) that injected huge amounts of smoke into the lower stratosphere. The pyroCbs from 29 December - 4 January were particularly intense, producing hemispheric-wide aerosol that persisted for months. One plume from this so-called Australian New Year (ANY) event evolved into a stratospheric aerosol mass ~1000 km across and several km thick. This plume initially moved eastward towards South America in January, then rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
68
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(92 citation statements)
references
References 0 publications
11
68
0
1
Order By: Relevance
“…It is easy to generate overestimates of rising rates from a structure moving over a fixed observatory. For instance, Ohneiser et al (2020), and yourself in your comment claim an ascent rate of 1km/day when Koobor was near the tip of South America which is about three time the ascent rate found by Khaykin et al (2020) (corroborated by Allen et al (2020)) at the same time on the trajectory. The ascent of Koobor was basically smooth for three months, es-pecially in potential temperature, except during two episodes of vertical split and it rose from about 16 km to 35 km, which is a considerable way against the Brewer-Dobson circulation but it did not reach the ionosphere.…”
mentioning
confidence: 64%
“…It is easy to generate overestimates of rising rates from a structure moving over a fixed observatory. For instance, Ohneiser et al (2020), and yourself in your comment claim an ascent rate of 1km/day when Koobor was near the tip of South America which is about three time the ascent rate found by Khaykin et al (2020) (corroborated by Allen et al (2020)) at the same time on the trajectory. The ascent of Koobor was basically smooth for three months, es-pecially in potential temperature, except during two episodes of vertical split and it rose from about 16 km to 35 km, which is a considerable way against the Brewer-Dobson circulation but it did not reach the ionosphere.…”
mentioning
confidence: 64%
“…This section provides a helpful reference of other papers that have studied this event. The PV anomaly associated with smoke during the Canadian event was also examined in a recent paper by Allen et al (2020). While that paper focused primarily on the "Koobor" vortex, they also included a PV anomaly map for 28 August 2017 associated with what this paper calls "Vortex A" (see Figure 16 of the following reference).…”
Section: Discussion Papermentioning
confidence: 99%
“…• Line 335: The northwest-southeast tilt of the PV increments for the Koobor vortex, shown in Figure 10a, is interesting. In the recent analysis by Allen et al (2020), they examined how Koobor tilts with height and found a NW-SE tilt of the vortex in January. They used a dynamical argument to show how this tilt may develop from internal vortex dynamics in a shear flow.…”
Section: Interactive Commentmentioning
confidence: 99%
See 2 more Smart Citations